Pós-modernidade e historiografia: Um estudo sobre Hayden White - Pedro Araujo Medeiros (2006)
Since the end of Second World War, a great acceleration in the scope of science and technique caused significant changes in all the other scopes of society. These changes, which in occidental world begun in 1945, were so important that marked the beginning of a new era, the postmodernity. In that context, scientific knowledge and, in a specific way, the historical knowledge, were modified. And what did 'make history' become in postmodernity? In the dialog between present time andnowadays historiography, our main study object is Hayden White, the historian that explores in the widest way the possibilities offered by postmodenrnity to the historiography. It is in the narrative of White that the postmodernity expresses itself with most intensity in the historical knowledge.